Surface energy contributions to the work of infiltration in metal matrix composite processing. (1st January 2022) - Molina-Jorda, José-Miguel; Schneider, Gionata; Mortensen, Andreas
Abstract: The work needed to mechanically drive molten metal into a porous solid preform when producing a composite material by infiltration can significantly exceed the energy change required for thermodynamically reversible infiltration. We measure, by quantitative metallographic analysis of partially infiltrated, particle- or fiber-based non-metallic preforms, the evolution with saturation of the three interfaces present during the process. Results show that irreversible energy losses in the infiltration of alumina preforms by molten copper, aluminium or aluminium-tin alloy cannot be ascribed to the creation of liquid meniscus surface area at intermediate metal saturation. This result agrees with similar observations in soil science and gives experimental confirmation of predictions from a recent simulation of capillarity-dominated metal infiltration [ Acta Mater., vol. 210, 2021, 116831]. Graphical abstract: Image, graphical abstract